Basophil activation can predict clinical sensitivity in patients after venom immunotherapy - Kučera, Petr; Cvačková, Milada; Hulíková, Katarína; Jůzová, Olga; Pachl, Jan (Journal of investigational allergology & clinical immunology, 2010)
OBJECTIVE: At present, no reliable in vitro test is available to monitor the success of specific venom immunotherapy (VIT) in preventing insect venom anaphylaxis. We investigated usefulness of the basophil activation test (BAT) in predicting the outcome of sting challenge in bee venom-allergic patients after VIT. PATIENTS AND METHODS: Twenty-one patients with bee venom anaphylaxis at the end of VIT and 6 control participants were enrolled. BAT (flow-cytometric evaluation of allergen-induced expression of CD63), skin testing, and specific immunoglobulin (Ig) E determination were performed prior to sting challenge. RESULTS: Five of the 21 patients (23.8%) reacted to sting challenge. At a bee venom concentration of 100 ng/mL, the mean proportion of basophils expressing CD63 was 56% in reactors and 13.2% in nonreactors (P = .0321). Four of the 5 reactors had positive results and 14 of the 16 nonreactors had negative results. Thus, using 18.4% and 21.6% (receiver operating characteristic curve analysis) as the cutoff for expression of the CD63 marker, the positive and the negative predictive values were 67% and 93%, respectively, and specificity and sensitivity for BAT were 80% and 83%, respectively. However, at a concentration of 1000 ng/mL, no significant differences in basophil activation were observed between reactors and nonreactors. CONCLUSION: We found BAT to be a helpful tool in predicting the clinical sensitivity of bee venom-allergic patients after VIT (correlation between BAT at submaximal venom concentration and sting challenge).
Keywords: Bee Venoms; glykoproteiny membrány trombocytů; Sensitivity and Specificity; Basophil Degranulation Test; Platelet Membrane Glycoproteins; senzitivita a specificita; lidé; Humans; prediktivní hodnota testů; průtoková cytometrie; lidé středního věku; Desensitization, Immunologic; Allergens; antigeny CD63; desenzibilizace imunologická; Middle Aged; Predictive Value of Tests; Tetraspanin 30; Female; Male; Adult; prognóza; Biomarkers; Prognosis; test degranulace bazofilů; separace buněk; mužské pohlaví; ženské pohlaví; Anaphylaxis; včelí jedy; bazofily; Antigens, CD; Cell Separation; dospělí; Basophils; biologické markery; CD antigeny; Flow Cytometry; alergeny; anafylaxe